Ocean light ebook - Singh, Nalini (Psy-Changeling Trinity, 2018)
New York Times bestselling author Nalini Singh dives beneath the surface of her Psy-Changeling world into a story of passionate devotion and selfless love...  Security specialist Bowen Knight has come back from the dead. But there’s a ticking time bomb in his head: a chip implanted to block telepathic interference that could fail at any moment—taking his brain along with it. With no time to waste, he should be back on land helping the Human Alliance. Instead, he’s at the bottom of the ocean, consumed with an enigmatic changeling.  Kaia Luna may have traded in science for being a chef, but she won’t hide the facts of Bo’s condition from him or herself. She’s suffered too much loss in her life to fall prey to the dangerous charm of a human who is a dead man walking. And she carries a devastating secret Bo could never imagine.  But when Kaia is taken by those who mean her deadly harm, all bets are off. Bo will do anything to get her back—even if it means striking a devil’s bargain and giving up his mind to the enemy…